Exploring Conceptual Metaphors in a Corpus of Sanggau Malay Songs: Cognitive Semantic Perspective - Syahrani, Agus; Irvansyah, Alif; Ermanto, Ermanto; Ardi, Havid; Asfar, Dedy Ari (Ranah: Jurnal Kajian Bahasa, 2025)
This study aims to analyze the forms and types of conceptual metaphors and image schemas found in the corpus of Malay Sanggau song lyrics using a cognitive semantic approach. This study uses a qualitative descriptive method with data sources in the form of a corpus of seven Malay Sanggau songs taken from YouTube channels: Pancur Aji, Posan Ini, Riyak Sekayam, Lanau Idau, Borita Kalengkang, Ngapai Kapuas, and Biar Gonting Inang Putus. Data were collected through audiovisual and digital document analysis, as well as interviews with native speakers of Malay Sanggau to verify meanings. The analysis process was carried out through the stages of transcription, translation, identification of metaphors based on Lakoff and Johnson's Conceptual Metaphor theory, and application of Croft and Cruse's Image Schema theory to find cognitive relationships between the source domain and the target domain. The results of the study show that in the Sanggau Malay song corpus, there are three orientational metaphors, three structural metaphors, and three ontological metaphors. Each type of metaphor describes how the Sanggau Malay community interprets their life experiences, emotions, and cultural values through figurative language. These findings reinforce the view that conceptual metaphors function as a mirror of the cognition and local cultural identity of the Sanggau Malay community. Abstrak Penelitian ini bertujuan untuk menganalisis bentuk dan jenis metafora konseptual dan skema citra yang terdapat dalam korpus lirik lagu Melayu Sanggau dengan menggunakan pendekatan semantik kognitif. Penelitian ini menggunakan metode deskriptif kualitatif dengan sumber data berupa korpus tujuh lagu Melayu Sanggau yang diambil dari kanal YouTube: Pancur Aji, Posan Ini, Riyak Sekayam, Lanau Idau, Borita Kalengkang, Ngapai Kapuas, dan Biar Gonting Inang Putus. Data dikumpulkan melalui analisis dokumen audiovisual dan digital, serta wawancara dengan penutur asli Melayu Sanggau untuk verifikasi makna. Proses analisis dilakukan melalui tahapan transkripsi, penerjemahan, identifikasi metafora berdasarkan teori Metafora Konseptual Lakoff dan Johnson dan penerapan teori Skema Citra Croft dan Cruse untuk menemukan hubungan kognitif antara domain sumber dan domain sasaran. Hasil penelitian menunjukkan bahwa dalam korpus lagu Melayu Sanggau terdapat tiga metafora orientasional, tiga metafora struktural, dan tiga metafora ontologis. Setiap jenis metafora menggambarkan cara masyarakat Melayu Sanggau memaknai pengalaman hidup, emosi, dan nilai budaya mereka melalui bahasa kiasan. Temuan ini memperkuat pandangan bahwa metafora konseptual berfungsi sebagai cermin kognisi dan identitas budaya lokal masyarakat Melayu Sanggau.